Oral microbiome composition is associated with depressive symptoms during pregnancy - Oryan Agranyoni; Treva Rowley; Sara B. Johnson; Heather Volk; William Schleif; Raquel G. Hernandez; Lauren M. Klein; Robert H. Yolken; Sarven Sabunciyan (Brain, Behavior, & Immunity - Health)
Background: Oral microbiome dysbiosis has been linked to systemic disease with an underlying inflammatory etiology. However, the possible association of the oral microbiome in antenatal depression has received little attention. Methods: Participants were pregnant women in the PREDICT prenatal cohort study (n = 400) who provided saliva during pregnancy. Using 16S rRNA sequencing, we determined the association between composition of the salivary microbiome and a continuous measure of depressive symptoms (Center for Epidemiological Studies-Depression Scale (CES-D): 0–60) as well as clinically significant depressive symptoms during pregnancy (CES-D score> 16, n = 46) compared with women without clinically significant symptoms (n = 327). Results: CES-D scores were associated with differences in bacterial levels in the salivary microbiome. Women with clinically significant depressive symptoms (CES-D≥16) had significantly lower abundance in nine bacterial taxa, including the Neisseria genus, which has previously been positively associated with oral health and negatively correlated with pro-inflammatory cytokines, mental health, and infant birth weight. Findings were not explained by body mass index, smoking, antibiotic administration, oral health problems, or gestational week. Prediction tools based on 16S sequences indicated that significantly lower levels of several pathways related to the biosynthesis of Menaquinol, Ectoine biosynthesis, and D-glucarate degradation, were associated with women with depressive symptoms. Conclusions: Our findings underscore the potential relationship between the oral microbiome and antenatal depression, highlighting microbiome measures as a promising source of biomarkers for maternal mental health. This study suggests previously unexplored aspects for understanding the microbiome's composition in women with mental health problems, emphasizing the need for further longitudinal investigations to elucidate the temporal dynamics of the oral microbiome in pregnancy.